Frequency and types of antibiotic usage in a referral neonatal intensive care unit, based on the world health organization classification (AwaRe) - Farzaneh Hematian; Seyyed Mohammad Hassan Aletayeb; Masoud Dehdashtian; Mohammad Reza Aramesh; Arash Malakian; Mahboobeh Sadat Aletayeb (BMC Pediatrics)
Abstract Background Excessive prescription of antibiotics in infants increases the risk of short-term and lifelong morbidity and mortality. Nonetheless, the use of antibiotics in neonatal intensive care units (NICUs) is significantly high. This is primarily because neonatologists are concerned about the fragile immune systems of newborns, their vulnerability to serious infectious diseases, and the challenge of accurately distinguishing between infectious and non-infectious conditions. Method A five-month cross-sectional prospective study was conducted in southwestern Iran’s largest neonatal intensive care unit. This study aimed to evaluate the dose and duration of antibiotic therapy and identify the prescribing pattern of antibiotics based on the Access, Watch, and Reserve (AWaRe) classification recommended by the World Health Organization (WHO). Results Out of 502 examined patient files, antibiotics were prescribed for 483 neonates. The most common drug combinations were ampicillin and amikacin. The mean number and duration of antibiotic administration were 2.14 drugs and 7.78 days, respectively. 84.3% of infants received antibiotics for ten days or less. The mean course of antibiotic prescription for newborns was 1.1, and 83.1% of prescribed antibiotics were from the Access Group. Conclusion The antibiotic prescription rate was high in our study’s department. Most neonates received two antibiotics in one course from the Access group.